2017
DOI: 10.1038/s41598-017-17293-2
|View full text |Cite
|
Sign up to set email alerts
|

Effective litmus gene test for monitoring the quality of blood samples: Application to Alzheimer’s disease diagnostics

Abstract: Gene expression profiles reflect the biologically diverse activities of cells under specific cell environments. Using the transcriptional response of cultured cells to blood composition, we developed a litmus gene assay to discriminate blood samples reflecting different sample qualities or disease conditions. This cell-based litmus gene assay identified six genes (CCL20, CEMIP, IL1B, IL8, PRG2, PTGS2) as potential biomarkers of plasma quality control and the SPC25 gene as a diagnostic biomarker of Alzheimer’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…In our research, we found that CCL20 acts as a protective factor against AD [51]. It has been reported that plasma from AD patients can inhibit the generation of CCL20 in vitro [52]. Additionally, the expression of CCL20 has been found to decrease in the plasma of AD mouse models [53].…”
Section: Discussionsupporting
confidence: 58%
“…In our research, we found that CCL20 acts as a protective factor against AD [51]. It has been reported that plasma from AD patients can inhibit the generation of CCL20 in vitro [52]. Additionally, the expression of CCL20 has been found to decrease in the plasma of AD mouse models [53].…”
Section: Discussionsupporting
confidence: 58%
“…The NF-κB pathway mediates the transcription of MIP-3α [27]. It has been reported that AD patients' plasma can suppress the generation of CCL20 in SHSY-5Y cell lines [28]. This suggests that there factors may influence the NF-κB pathway and induce immunologic abnormalities in the peripheral system in the development of tau pathology.…”
Section: Discussionmentioning
confidence: 99%
“…MIP-3α is a chemokine for immature dendritic cells. The NF-κB pathway mediates the transcription of MIP-3α [27].It has been reported that AD patients' plasma can suppress the generation of CCL20 in SHSY-5Y cell lines [28]. This suggests there factors may influence the NF-κB pathway and induce immunologic abnormalities in the peripheral system in the development of tau pathology.…”
Section: Discussionmentioning
confidence: 99%